Doctors and Witches, Conscience and Violence: Abortion Provision on American Television. Issue 4 (29th September 2016) - Sisson, Gretchen; Kimport, Katrina
Abstract : CONTEXT: Popular entertainment may reflect and produce—as well as potentially contest—stigma regarding abortion provision. Knowledge of how providers are portrayed on‐screen is needed to improve understanding of how depictions may contribute to the stigmatization of real providers. METHODS: All abortion provision plotlines on American television from 2005 to 2014 were identified through Internet searches. Plotlines were assessed in their entirety and coded for genre, abortion provision space, provider characteristics, method and efficacy of provision, and occurrence of violence. Inductive content analysis was used to identify themes in how these features were depicted. RESULTS: Fifty‐two plotlines involving abortion provision were identified on 40 television shows; a large majority of plotlines appeared in dramas, particularly in the subgenre of medical dramas. Medical spaces were depicted as normal and safe for abortion provision, and nonmedical spaces were often portrayed as remote and unsafe. Legal abortion care using medical methods was depicted as effective and safe, and legal providers were presented as compassionate, while providers operating outside of medical and legal authority were depicted as ineffective, dangerous and uncaring. Fictional providers were largely motivated by the belief that abortion provision is a necessary and moral service. Plotlines linked abortion provision to violence. CONCLUSIONS: The differing ways in which legal and illegal abortion are portrayed reveal potential consequences regarding real‐world abortion provision, and suggest that representations situated in medical contexts may work to legitimate and destigmatize such provision.